Pengaruh Lingkungan Kerja Dan Disiplin Kerja Terhadap Kinerja Karyawan PT. Infomedia Nusantara Bagian Call Center Tele Account Management (TAM) Telkom Bandung - Dewi Puspita Sari; Imelda Megawati; Imam Heryanto (Majalah Bisnis & IPTEK, 2020)
This research aims to find and analyze the impact of the work environment and work discipline on employee performance. This study uses descriptive analysis and verification analysis with 75 respondents. Besides, this study uses path analysis. The result shows that the work environment is adequate, the result of the work discipline is acceptable, and employee performance is decent. The direct and indirect effect of the work environment on performance is 0,458. The direct and indirect effect of work discipline on performance is 0,303. The entire effect is 0,761. Coefficient determination is 76,1%, and the rest is 24,0% from the other variables that affect employee performance, but they are not analyzed in this study.